2021
DOI: 10.1002/ejp.1849
|View full text |Cite
|
Sign up to set email alerts
|

Are mindfulness treatments effective for pain in cancer patients? A systematic review and meta‐analysis

Abstract: Background and objective Mindfulness‐based interventions (MBIs) have been recently applied in pain management and cancer care. However, inconsistencies exist concerning the effectiveness of MBIs on pain control among cancer patients. Therefore, this study aimed to examine the efficacy of MBIs on pain in cancer patients via a systematic review and meta‐analysis of randomized controlled trials (RCTs). Methods Databases (MEDLINE, PubMed, Embase, CINAHL, PsycINFO, Cochrane Central Register of Controlled Trials and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…According to the evaluation of treatments, 11SRs [ 37 47 ] only evaluated CBT-related techniques, 11 SRs [ 34 , 48 57 ] also evaluated other psychological therapies, 5 SRs [ 58 62 ] evaluated nonpharmacological interventions in addition to psychological therapies, 2 SRs [ 35 , 63 ] evaluated pharmacological and nonpharmacological interventions, and 5 SRs [ 36 , 64 67 ] evaluated various interventions. Of the available data, 15 SRs [ 38 40 , 43 45 , 47 , 50 , 53 57 , 63 , 65 ] included migraine, 7 SRs [ 34 , 35 , 52 , 60 , 64 , 66 , 67 ] included burning mouth syndrome, 4 SRs [ 36 , 42 , 46 , 62 ] included cancer-related neuropathic pain, 3 SRs [ 51 , 59 , 61 ] included diabetic peripheral neuropathy, 3 SRs [ 48 , 49 , 58 ] included pain after spinal cord injury, and 2 SRs [ 37 , 41 ] included patients with NP of different causes.…”
Section: Resultsmentioning
confidence: 99%
“…According to the evaluation of treatments, 11SRs [ 37 47 ] only evaluated CBT-related techniques, 11 SRs [ 34 , 48 57 ] also evaluated other psychological therapies, 5 SRs [ 58 62 ] evaluated nonpharmacological interventions in addition to psychological therapies, 2 SRs [ 35 , 63 ] evaluated pharmacological and nonpharmacological interventions, and 5 SRs [ 36 , 64 67 ] evaluated various interventions. Of the available data, 15 SRs [ 38 40 , 43 45 , 47 , 50 , 53 57 , 63 , 65 ] included migraine, 7 SRs [ 34 , 35 , 52 , 60 , 64 , 66 , 67 ] included burning mouth syndrome, 4 SRs [ 36 , 42 , 46 , 62 ] included cancer-related neuropathic pain, 3 SRs [ 51 , 59 , 61 ] included diabetic peripheral neuropathy, 3 SRs [ 48 , 49 , 58 ] included pain after spinal cord injury, and 2 SRs [ 37 , 41 ] included patients with NP of different causes.…”
Section: Resultsmentioning
confidence: 99%
“…Another recent meta‐analysis by Feng and colleagues 66 demonstrated that MBIs were associated with significant improvements in pain intensity among patients with cancer at both short‐term and long‐term follow‐up, albeit with a small effect size. The improvements were more significant in face‐to‐face settings than with internet‐based or remote delivery 66 . Still, there may be a role for app‐delivered MBIs in pain reduction.…”
Section: Mindfulness and Inflammation Pain And Social Functioningmentioning
confidence: 99%
“…Only four studies in that meta‐analysis reported on analgesic use as an outcome, and results were mixed, with two studies showing a decrease in analgesic use after an MBI 64 . Another recent meta‐analysis by Feng and colleagues 66 demonstrated that MBIs were associated with significant improvements in pain intensity among patients with cancer at both short‐term and long‐term follow‐up, albeit with a small effect size. The improvements were more significant in face‐to‐face settings than with internet‐based or remote delivery 66 .…”
Section: Mindfulness and Inflammation Pain And Social Functioningmentioning
confidence: 99%
See 2 more Smart Citations